Sex-specific extracerebral complications in patients with aneurysmal subarachnoid hemorrhage - Bögli, Stefan Y.; Beham, Sabrina; Hirsbrunner, Laura; Nellessen, Friederike; Casagrande, Francesca; Keller, Emanuela; Brandi, Giovanna (Frontiers in Neurology, 2023)
Background Extracerebral complications in patients with aneurysmal subarachnoid hemorrhage (aSAH) often occur during their stay at the neurocritical care unit (NCCU). Their influence on outcomes is poorly studied. The identification of sex-specific extracerebral complications in patients with aSAH and their impact on outcomes might aid more personalized monitoring and therapy strategies, aiming to improve outcomes. Methods Consecutive patients with aSAH admitted to the NCCU over a 6-year period were evaluated for the occurrence of extracerebral complications (according to prespecified criteria). Outcomes were assessed with the Glasgow Outcome Scale Extended (GOSE) at 3 months and dichotomized as favorable (GOSE 5–8) and unfavorable (GOSE 1–4). Sex-specific extracerebral complications and their impact on outcomes were investigated. Based on the results of the univariate analysis, a multivariate analysis with unfavorable outcomes or the occurrence of certain complications as dependent variables was performed. Results Overall, 343 patients were included. Most of them were women (63.6%), and they were older than men. Demographics, presence of comorbidities, radiological findings, severity of bleeding, and aneurysm-securing strategies were compared among the sexes. More women than men suffered from cardiac complications (p = 0.013) and infection (p = 0.048). Patients with unfavorable outcomes were more likely to suffer from cardiac (p < 0.001), respiratory (p < 0.001), hepatic/gastrointestinal (p = 0.023), and hematological (p = 0.021) complications. In the multivariable analysis, known factors including age, female sex, increasing number of comorbidities, increasing World Federation of Neurosurgical Societies (WFNS), and Fisher grading were expectedly associated with unfavorable outcomes. When adding complications to these models, these factors remained significant. However, when considering the complications, only pulmonary and cardiac complications remained independently associated with unfavorable outcomes. Conclusion Extracerebral complications after aSAH are frequent. Cardiac and pulmonary complications are independent predictors of unfavorable outcomes. Sex-specific extracerebral complications in patients with aSAH exist. Women suffered more frequently from cardiac and infectious complications potentially explaining the worse outcomes.